A STUDY ON PROXIMATE COMPOSITION, AMINO ACID PROFILE, FATTY ACID PROFILE AND SOME MINERAL CONTENTS IN TWO SPECIES OF SEA CUCUMBER - M. S. Haider; R. Sultana; K. Jamil; Lakht-e-Zehra; O. M. Tarar; K. Shirin; W. Afzal (Journal of Animal and Plant Sciences, 2015)
Coastal waters of Pakistan have considerable biodiversity of sea cucumbers and to date 11 genera and fifteen species of sea cucumbers belonging to 3 families have been recorded. In the present study the biochemical composition and nutritional quality of two most common sea cucumbers (Holothuria arenicola and Actinopyga mauritiana) were determined. The study includes their proximate, amino acid, and fatty acid compositions. The protein content of Actinopyga mauritiana is ~ 67 % comparatively higher than that of Holothuria arenicola, in which it was ~ 45 %. The high value for ash content was found in H. arenicola i.e. ~45 % in comparison to ~32 % in A. mauritiana, The lipid content was not significantly different in the two species and attained values of 0.88 % and 0.76 % in H. arenicola and A. mauritiana, respectively. The total fatty acids were determined for both the species in which findings suggested that polyunsaturated fatty acid (PUFA) was more than saturated fatty acid (SFA) and monounsaturated fatty acid (MUFA). Results also showed that eicosapentaenoic acid (EPA; 20:5ω3), arachidonic acid (AA; 20:4ω6) and docosahexaenoic acid (DHA; 22:6ω3) are dominant among all PUFA. All the essential amino acids were found in both the species in which Glycine was found as major amino acid. Profile also suggested that Lysine/Arginine ratio was in favorable range to produce Hypocholesterolemic and antiatherogenic effects. Both the species of sea cucumbers are potential source of macro and micro nutrients with having no toxic elements under studied. .
Keywords: sea cucumber; biochemical composition; essential amino acid; total fatty acids